STUDI DESKRIPTIF MEMBACA PERMULAAN DI KELAS I-B SDN PANCORAN 07 PAGI TAHUN AJARAN 2019/2020 - Lola Sarah Aulia; Robiatul Munajah (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2021)
This study aims to describe the inhibiting and supporting factors of prefix reading, as well as to describe the teacher's efforts in overcoming pre-reading problems in class I-B SDN Pancoran 07 Pagi. This research uses a qualitative approach with descriptive methods. Data collection techniques in this study were interviews and observation. The results of this study indicate that there are several inhibiting factors such as: (1) lack of self-confidence, (2) low learning concentration, (3) lack of teacher assertiveness, (4) lack of parental attention. The supporting factors for reading the beginning are: (1) supporting facilities and infrastructure, (2) the existence of a reading corner, (3) peers. While the teacher's efforts that have been made are: (1) The teacher provides additional hours, (2) The learning process is fun.